Hot deformation behaviour and microstructure of a high-alloy gear steel. Issue 10 (3rd July 2018) - Tang, Haiyan; Yang, Maosheng; Meng, Wenjia; Lan, Peng; Wang, Chen
ABSTRACT: High strain isothermal compression tests at temperatures of 700–1200°C and strain rates of 0.1–50 s −1 were performed in a Gleeble-3800 thermal simulator to investigate the hot deformation behaviour of a high-alloy Cr–Co–Mo–Ni gear steel, and the constitution equation and hot processing map were established based on these experiments. The results show that the flow stress can be described by the constitutive equation in hyperbolic sine function, and the optimum hot working regions are at the temperature of 1000–1100°C and strain rate of 0.3–1.0 s −1 . Optical microscopy observations of austenite grains indicate that dynamic recrystallisation occurs when the deformation temperature is over 900°C. The forging was successfully produced on the basis of the above-described researches.